2003
DOI: 10.1038/sj.mp.4001220
|View full text |Cite
|
Sign up to set email alerts
|

Phospho-tau/total tau ratio in cerebrospinal fluid discriminates Creutzfeldt–Jakob disease from other dementias

Abstract: Early clinical symptoms of sporadic Creutzfeldt-Jakob disease (CJD) may overlap with other neurodegenerative diseases like Alzheimer's disease (AD) and frontotemporal degeneration (FTD). On entering an era in which pharmaceutical treatment of CJD occurs, reliable diagnostic markers like immunodetection of 14-3-3 proteins in the cerebrospinal fluid (CSF) are required. However, false negative results in autopsy-proven, sporadic CJD cases, as well as false positive results in several other disorders including AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
134
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(158 citation statements)
references
References 20 publications
19
134
2
3
Order By: Relevance
“…The extremely high levels of t-tau that we found in sCJD patients are in accordance with other studies [5,14,22,28,32,38,39], with sensitivity (87-94%) and specificity (90-100%) figures similar to ours. In fact, t-tau has been suggested to be the most sensitive marker in early stage sCJD [33].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The extremely high levels of t-tau that we found in sCJD patients are in accordance with other studies [5,14,22,28,32,38,39], with sensitivity (87-94%) and specificity (90-100%) figures similar to ours. In fact, t-tau has been suggested to be the most sensitive marker in early stage sCJD [33].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, associating ttau with p-tau (p-tau/t-tau ratio) improved the sensitivity of the t-tau test alone (from 90% to 93%), but not its specificity (95%). This is in line with previous studies, reporting comparable sensitivity (78-100%) and specificity (93-100%) [2,5,28,32]. The increase in CSF S-100b levels observed in sCJD patients has been previously reported, but the absolute values are difficult to compare as different methodologies have been employed [14,30,31].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a recent study, the ratio of tau protein phosphorylated at threonine 181 and t-tau had been suggested as a useful measurement to identify patients with CJD [16]. In agreement with that study, we found that the p-tau/t-tau ratio was lowest in the CJD group compared to the other groups studied.…”
Section: Discussionsupporting
confidence: 91%
“…Measurement of CSF p-tau 181 , however, did not improve diagnostic power between CJD and AD compared to measurement of t-tau [20]. Another study showed an overlap of CSF p-tau 181 concentrations between AD and CJD patients and suggested the p-tau 181 /t-tau ratio as a potential biomarker to differentiate CJD from AD [16].…”
Section: Introductionmentioning
confidence: 96%